KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI OLEH DOKTER GIGI SELAMA PANDEMI COVID-19 (HIGEIA (Journal of Public Health Research and Development), 2022)
During the Covid-19 pandemic, compliance with the use of Personal Protective Equipment (PPE) received special attention, especially in hospitals and as medical personnel. In practice, the level of compliance of dentists in carrying out standard precautions, especially personal protective equipment (PPE) is still lacking. This study aims to analyze the factors related to compliance with the use of personal protective equipment (PPE) in dentists at RSIGM Sultan Agung Semarang. This study was a cross sectional study of 51 dentists at RSIGM Sultan Agung Semarang in June-December 2021. The results of the study showed a relationship between clarity of information (p value = 0.000) and leadership (p value = 0.000) on compliance with the use of personal protective equipment (p value = 0.000) PPE). And there is no relationship between years of service (p value = 0.198) and gender (p = value = 0.162), with the most gender being female (80.4%). Therefore, it is recommended that dentists comply with the use of personal protective equipment (PPE), because personal protective equipment does not hinder the services provided to patients.